Common α-Fuzzy Fixed Point Results for Kannan Type Contractions with Application. (17th May 2022) - Albargi, Amer Hassan; Ahmad, Jamshaid
Abstract : The purpose of this paper is to utilize complex valued extended b -metric space and obtain common α -fuzzy fixed point theorems under Kannan type contractions. As application, we derive common α -fixed point results for multivalued mappings in the context of complex valued extended b -metric space.